The ratio of the sides will be constant. Then the value of the length of line segment SA will be 3 ft.
The missing diagram is given below.
<h3>What is the triangle?</h3>
A triangle is a three-sided polygon with three angles. The angles of the triangle add up to 180 degrees.
The triangles ΔABC and ΔSBT are the similar triangles.
Then the ratio of the sides will be constant.
BS / SA = BT / TC
10 / SA = 9 / 2.7
SA = 3
Then the value of the length of line segment SA will be 3 ft.
More about the triangle link is given below.
brainly.com/question/25813512
#SPJ1
Answer:
His actual score is 15
Step-by-step explanation:
Here, we are interested in calculating Wayne’s actual score on the ACT
when we say the scores have being standardized, it means the score was reported in terms of the z-score and not the initial raw scores.
Now, mathematically, for the scores to have a negative z-score, it means it is actually below the mean.
The formula for the z-score or standard score is given below;
z-score = (x - mean)/SD
where in this case, x = ? which is the score we are looking for , z-score = -0.5 , mean score = 18 and standard deviation of the scores = 6
So, substituting these values into the z-score equation, we have;
-0.5 = (x-18)/6
x-18 = 6(-0.5)
x -18 = -3
x = -3 + 18
x = 15
Answer:x=1
Step-by-step explanation:
y=y
y = -x + 10
y = 7x + 2
-x+10=7x+2
10=8x+2
8=8x
x=1
Answer: The required solution is
![y(t)=-\dfrac{7}{3}e^{-t}+\dfrac{7}{3}e^{\frac{1}{5}t}.](https://tex.z-dn.net/?f=y%28t%29%3D-%5Cdfrac%7B7%7D%7B3%7De%5E%7B-t%7D%2B%5Cdfrac%7B7%7D%7B3%7De%5E%7B%5Cfrac%7B1%7D%7B5%7Dt%7D.)
Step-by-step explanation: We are given to solve the following differential equation :
![5y^{\prime\prime}+3y^\prime-2y=0,~~~~~~~y(0)=0,~~y^\prime(0)=2.8~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://tex.z-dn.net/?f=5y%5E%7B%5Cprime%5Cprime%7D%2B3y%5E%5Cprime-2y%3D0%2C~~~~~~~y%280%29%3D0%2C~~y%5E%5Cprime%280%29%3D2.8~~~~~~~~~~~~~~~~~~~~~~~~%28i%29)
Let us consider that
be an auxiliary solution of equation (i).
Then, we have
![y^prime=me^{mt},~~~~~y^{\prime\prime}=m^2e^{mt}.](https://tex.z-dn.net/?f=y%5Eprime%3Dme%5E%7Bmt%7D%2C~~~~~y%5E%7B%5Cprime%5Cprime%7D%3Dm%5E2e%5E%7Bmt%7D.)
Substituting these values in equation (i), we get
![5m^2e^{mt}+3me^{mt}-2e^{mt}=0\\\\\Rightarrow (5m^2+3y-2)e^{mt}=0\\\\\Rightarrow 5m^2+3m-2=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~[\textup{since }e^{mt}\neq0]\\\\\Rightarrow 5m^2+5m-2m-2=0\\\\\Rightarrow 5m(m+1)-2(m+1)=0\\\\\Rightarrow (m+1)(5m-1)=0\\\\\Rightarrow m+1=0,~~~~~5m-1=0\\\\\Rightarrow m=-1,~\dfrac{1}{5}.](https://tex.z-dn.net/?f=5m%5E2e%5E%7Bmt%7D%2B3me%5E%7Bmt%7D-2e%5E%7Bmt%7D%3D0%5C%5C%5C%5C%5CRightarrow%20%285m%5E2%2B3y-2%29e%5E%7Bmt%7D%3D0%5C%5C%5C%5C%5CRightarrow%205m%5E2%2B3m-2%3D0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~%5B%5Ctextup%7Bsince%20%7De%5E%7Bmt%7D%5Cneq0%5D%5C%5C%5C%5C%5CRightarrow%205m%5E2%2B5m-2m-2%3D0%5C%5C%5C%5C%5CRightarrow%205m%28m%2B1%29-2%28m%2B1%29%3D0%5C%5C%5C%5C%5CRightarrow%20%28m%2B1%29%285m-1%29%3D0%5C%5C%5C%5C%5CRightarrow%20m%2B1%3D0%2C~~~~~5m-1%3D0%5C%5C%5C%5C%5CRightarrow%20m%3D-1%2C~%5Cdfrac%7B1%7D%7B5%7D.)
So, the general solution of the given equation is
![y(t)=Ae^{-t}+Be^{\frac{1}{5}t}.](https://tex.z-dn.net/?f=y%28t%29%3DAe%5E%7B-t%7D%2BBe%5E%7B%5Cfrac%7B1%7D%7B5%7Dt%7D.)
Differentiating with respect to t, we get
![y^\prime(t)=-Ae^{-t}+\dfrac{B}{5}e^{\frac{1}{5}t}.](https://tex.z-dn.net/?f=y%5E%5Cprime%28t%29%3D-Ae%5E%7B-t%7D%2B%5Cdfrac%7BB%7D%7B5%7De%5E%7B%5Cfrac%7B1%7D%7B5%7Dt%7D.)
According to the given conditions, we have
![y(0)=0\\\\\Rightarrow A+B=0\\\\\Rightarrow B=-A~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)](https://tex.z-dn.net/?f=y%280%29%3D0%5C%5C%5C%5C%5CRightarrow%20A%2BB%3D0%5C%5C%5C%5C%5CRightarrow%20B%3D-A~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~%28ii%29)
and
![y^\prime(0)=2.8\\\\\Rightarrow -A+\dfrac{B}{5}=2.8\\\\\Rightarrow -5A+B=14\\\\\Rightarrow -5A-A=14~~~~~~~~~~~~~~~~~~~~~~~~~~~[\textup{Uisng equation (ii)}]\\\\\Rightarrow -6A=14\\\\\Rightarrow A=-\dfrac{14}{6}\\\\\Rightarrow A=-\dfrac{7}{3}.](https://tex.z-dn.net/?f=y%5E%5Cprime%280%29%3D2.8%5C%5C%5C%5C%5CRightarrow%20-A%2B%5Cdfrac%7BB%7D%7B5%7D%3D2.8%5C%5C%5C%5C%5CRightarrow%20-5A%2BB%3D14%5C%5C%5C%5C%5CRightarrow%20-5A-A%3D14~~~~~~~~~~~~~~~~~~~~~~~~~~~%5B%5Ctextup%7BUisng%20equation%20%28ii%29%7D%5D%5C%5C%5C%5C%5CRightarrow%20-6A%3D14%5C%5C%5C%5C%5CRightarrow%20A%3D-%5Cdfrac%7B14%7D%7B6%7D%5C%5C%5C%5C%5CRightarrow%20A%3D-%5Cdfrac%7B7%7D%7B3%7D.)
From equation (ii), we get
![B=\dfrac{7}{3}.](https://tex.z-dn.net/?f=B%3D%5Cdfrac%7B7%7D%7B3%7D.)
Thus, the required solution is
![y(t)=-\dfrac{7}{3}e^{-t}+\dfrac{7}{3}e^{\frac{1}{5}t}.](https://tex.z-dn.net/?f=y%28t%29%3D-%5Cdfrac%7B7%7D%7B3%7De%5E%7B-t%7D%2B%5Cdfrac%7B7%7D%7B3%7De%5E%7B%5Cfrac%7B1%7D%7B5%7Dt%7D.)
Answer:
sharon
Step-by-step explanation: